Sensecam as an Aid for Autobiographical Memory in an Amnesic Patient and Other Applications - Berry, Emma; Browne, Georgina; Kapur, Narinder; Wilson, Barbara; Williams, Lyndsay; Hodges, Steve; Woodberry, Ken (Microsoft Research, 2006)
SenseCam as an aid for autobiographical memory in anamnesic patient & other clinical applications.
Presentation at the 3rd Satellite Symposium on Neuropsychological Rehabilitation, Liechtenstein